The histamine H4 receptor: from orphan to the clinic - Thurmond, Robin L. (Frontiers in Pharmacology, 2015)
The histamine H4 receptor (H4R) was first noted as a sequence in genomic databases that had features of a G-protein coupled receptor. This putative receptor was found to bind histamine consistent with its homology to other histamine receptors and thus became the fourth member of the histamine receptor family. Due to the previous success of drugs that target the H1 and H2 receptors, an effort was made to understand the function of this receptor and determine if it represented a drug target. Taking advantage of the vast literature on histamine, a search for histamine activity that did not appear to be mediated by the other three histamine receptors was undertaken. From this asthma and pruritus emerged as areas of particular interest. Histamine has long been suspected to play a role in the pathogenesis of asthma, but antihistamines that target the H1 and H2 receptors have not been shown to be effective for this condition. The use of selective ligands in animal models of asthma has now potentially filled this gap by showing a role for the H4R in mediating lung function and inflammation. A similar story exists for chronic pruritus associated with conditions such as atopic dermatitis. Antihistamines that target the H1 receptor are effective in reducing acute pruritus, but are ineffective in pruritus experienced by patients with atopic dermatitis. As for asthma, animal models have now suggested a role for the H4R in mediating pruritic responses, with antagonists to the H4R reducing pruritus in a number of different conditions. The anti-pruritic effect of H4R antagonists has recently been shown in human clinical studies, validating the preclinical findings in the animal models. A selective H4R antagonist inhibited histamine-induced pruritus in health volunteers and reduced pruritus in patients with atopic dermatitis. The history to date of the H4R provides an excellent example of the deorphanization of a novel receptor and the translation of this into clinical efficacy